The early Holocene vegetation history and quantitative reconstruction of climate in the Chahanur Lake, Inner Mongolia Plateau, China - Zhang, Xu-Ran; Zhang, Hua-Yong; Wang, Zhong-Yu; Chen, Hao; Wu, Xiao-Chang; Liu, Zhao (Palaeoworld, 2025)
Vegetation is sensitive to climate change, and lake sediments store much information about palaeovegetation. Although environmental information has been recorded for most of the world’s lakes, some vegetation and climate history inconsistencies have persisted since the Holocene due to large regional differences. In this study, sediment samples were collected from Chahanur Lake on the Inner Mongolia Plateau, the dating sequence of the samples was determined by Accelerator Mass Spectrometry (AMS) 14C dating, and the vegetation history was reconstructed using the biome method and the climate was reconstructed using the weighted averaging partial least squares (WAPLS) method. Vegetation and climate history were systematically analysed. The results showed that the profile age of the lake was 11438–7918 cal. yr BP. During the early Holocene, vegetation evolved from sparse forest steppe (11438–10092 cal. yr BP) to broad-leaved forest steppe (10092–9288 cal. yr BP), and finally to the sparse forest steppe (9288–7918 cal. yr BP). Climate changed from cold and dry during 11438–10092 cal. yr BP, to warm and wet between 10092 and 9288 cal. yr BP, then warm and dry from 9288 to 7918 cal. yr BP. The reconstruction of palaeovegetation and palaeoclimate indicates increased precipitation during the early Holocene on the Inner Mongolia Plateau. This supports previous studies on palaeovegetation and enriches the Holocene pollen database.